Radical Love: Teachings from the Islamic Mystical Tradition By Omid Safi, trans. and ed. (New Haven: Yale University Press, 2018. 335 pages.) (American Journal of Islam and Society, 2019)
Collections of poems from the Islamic mystical tradition are not at all unusual on the American market. Yet most of these collections have been published by presses that specialize in spirituality, so it is quite remarkable to see this collection of poetry translated and edited by Omid Safi being published by Yale University Press. Safi is a Professor of Islamic Studies in the Department of Asian and Middle Eastern Studies at Duke University in North Carolina, and he is author of numerous books such as Progressive Muslims (2003), The Politics of Knowledge in Premodern Islam (2006) and Memories of Muhammad: Why the Prophet Matters (2009). Yet he is prob-ably better known as a public intellectual through his blogs and columns.To download full review, click on PDF.